Pemahaman materi vektor guru matematika prajabatan - Tamba, Kimura Patar (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
Vector is an important concept in mathematics. Pre-service mathematics teachers explore vector concepts in several courses. This concept is also related to various concepts in mathematics. The purpose of this study is to describe the pre-service mathematics teachers' understanding of vectors. This research is non-experimental research with a descriptive design. 67 pre-service mathematics teachers are participants in this study. Data were collected by survey method using the Test of Understanding of Vector instrument. Data analysis was carried out quantitatively using descriptive and inferential statistics. The descriptive statistics used are the average, maximum, minimum, and standard deviation. The inferential statistics used are t-test statistics. The results showed that in general, the pre-service mathematics teachers' understanding of vectors was in the medium category. The results also show that there is no difference in understanding of vectors between male and female pre-service mathematics teachers. However, in the two concepts, namely